(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Hyperbilirubinemia is a common problem in the neonatal period. Phototherapy is the most important proposed treatments for hyperbilirubinemia, but several drugs along with phototherapy are used with recent advances. Aim: To see the effect of oral fenofibrate on serum bilirubin level in term neonates with unconjugated hyperbilirubinaemia. Methods: This prospective study was carried out in Combined Military Hospital Cumilla from July 2018 to June 2019. Total 60 term and normal birth weight neonates with neonatal jaundice were enrolled in this study. Jaundiced newborns presenting with infection, G6PD deficiency, conjugated bilirubin >2 mg/dl or >15% of total serum bilirubin (TSB) and congenital anomalies were excluded from this study. These neonates were randomly allocated to the Fenofibrate group (30 cases) and Control group (30 cases). Total serum bilirubin was measured every 24 hours till the end of phototherapy and at the time of discharge. Statistical analysis was done using SPSS 22.0 and p<0.05 was considered significant. Results: There were no significant differences in gender, age, weight, gestational age and type of delivery between two groups. Mean duration of hospital stay were 4.0±0.7 and 5.5±1.4 days in Fenofibrate group and Control group respectively (p<0.001). In Fenofibrate group, TSB was decreased from 17.2 mg/dl to 15.2 mg/dl after 24 hours, to 13.6 mg/dl after 48 hours, and to 10.1 mg/dl at the time of discharge. In control group, TSB was decreased from 17.0 mg/dl to 16.3 mg/dl after 24 hours, to 15.9 mg/dl after 48 hours, and to 10.3 mg/dl at the time of discharge. Conclusion: Treatment of neonatal unconjugated hyper- bilirubinemia with fenofibrate reduces neonatal bilirubin levels and decreases the need for phototherapy and hospitalization. JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 35-38